Discovery of Bangladesh : explorations into dynamics of a hidden nation - Khan, Akbar Ali, 1944- (Dhaka, Bangladesh : University Press Limited, 1996)
Historical development of rural settlements, political instability, and proselytization in Bangladesh.
Includes bibliographical references (p. [161]-169) and index.
Keywords: Bangladesh -- History; Bengal (India) -- History